Regional-scale inventory of periglacial moving landforms connected to the torrential network system. - Kummert, Mario; Delaloye, Reynald (Geographisch-Ethnographische Gesellschaft Zürich, 2018)
When connected to torrential channels, periglacial moving landforms - including rock glaciers, push moraines and high-altitude landsliding masses - may constitute important active sediment sources for gravitational and torrential transfer processes such as debris flows. However, still very little is known about the location and the number of such types of sedimentary connection in given regions, as well as about the typical sediment transfer rates that can be expected. Therefore, this contribution aims at describing a new methodology developed to identify and characterize moving landforms connected to the torrential network system at a regional scale and presenting the results yielded from the application of this method in a 2000 km2 region in the southwestern Swiss Alps. The developed approach is based on the analysis of simple data such as a high-resolution digital elevation model (DEM), time series of aerial images and a slope movement inventory. The approach allowed both the fast identification of moving landforms connected to torrential channels and the estimation of annual sediment transfer rates for these inventoried landforms. In the study region, results showed that such types of sedimentary connection appeared to be rather rare. Results also showed that most connected moving landforms were characterized by relatively low sediment transfer rates but several sites were identified as transferring large amounts of sediment into the torrents. As sediment transfer rates depend on the kinematical behavior of the landforms, values calculated may change in regard to the evolution of the surface velocities, which are currently generally increasing in the European Alps. When connected to torrents, periglacial moving landforms may thus represent substantial active sources of sediments for the development of debris flows and should be considered in the management of torrential catchments.
Keywords: Gebirge; Gletscher; Erdbewegung; Moräne; Erdrutsch; Lawine; Sediment; Geröll; Geschiebe; Monitoring; Klimawandel